Potensi Legum Pohon â€œDemaâ€ Asal Kabupaten Sarmi Papua Sebagai Hijauan Pakan: The Potential of Dema Tree Legume in Sarmi Papua as a Forage - Diana Sawen; Luki Abdullah (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2020)
Abstract A preliminary study was carried out to determine the potential of dema tree legumes from Sarmi Papua as forage. Dema is the name of the local language for this legume. This study was conducted for 10 months in Sarmi regency, using a case study method with survey techniques, interviews, and laboratory analysis. The observations made included identification of species, morphology, and habitat as well as nutrient content. The results of this study indicate that there are two species of dema legume, the morphology was different in habitat description and leaf morphology. Propagations are by stem cuttings and seeds. The legumes nutritional content are 18.87% crude protein, 16.18% crude fiber, 3.97% calcium, and 17 amino acids. Forage production is around 2-4 kg/tree/3 months. Species identified as Ormocarpum orientale. The conclusion is dema legume has potential as forages. Keywords : Forages; Legumes; Potency; Sarmi Abstrak Suatu studi awal telah dilakukan untuk mengetahui potensi leguminosa pohon â€œdemaâ€ asal Kabupaten Sarmi Propinsi Papua sebagai hijauan pakan. Dema merupakan nama dari bahasa lokal untuk menyebut legume ini. Studi dilakukan selama 10 bulan, bertempat di kabupaten Sarmi, menggunakan metode studi kasus dengan teknik survei, wawancara dan analisis laboratorium. Pengamatan yang dilakukan meliputi identifikasi spesies, morfologi dan habitat serta kandungan gizi. Hasil studi menunjukkan bahwa terdapat 2 spesies legume dema, morfologinya spesifik pada deskripsi habitat dan morfologi daun. Perkembangbiaknnya dengan stek batang dan biji. Selanjutnya legume dema memiliki kandungan protein kasar sebesar 18,87%, serat kasar 16,18%, Kalsium (Ca) 3,97% dan juga 17 asam amino. Produksi hijauannya, 2-4 kg/pohon/3 bulan dan spesies teridentifikasi dengan nama Ormocarpum orientale. Dengan demikian berpotensi sebagai hijauan pakan. Kata kunci: Hijauan pakan; Legume pohon; Potensi; Sarmi